Tracing the magnetic field and other properties of G351.417+0.645 at subarcsecond scales with the Long Baseline Array. Issue 2 (12th October 2018) - Chanapote, T; Asanok, K; Dodson, R; Rioja, M; Green, J A; Hutawarakorn Kramer, B
ABSTRACT: We present the results from the Australian Long Baseline Array (LBA) observations of the ground- and excited-state OH masers (1.7- and 6.0-GHz lines) at high spatial and velocity resolution towards the high-mass star-forming region G351.417+ 0.645. We obtained accurate spatial gradient magnetic fields from 21 and 23 Zeeman pairs at ground and excited states, respectively, providing magnetic field measurements between −6.4 and +4.4 mG. In addition, we verify the reliability of magnetic field strengths measured from previous lower resolution observations. We found that OH maser features at 1665- and 6035-MHz reveal the same trend of a reversal of magnetic field which we attribute, based on recent infrared observations to cloud fragmentation. In comparison with previous LBA observations 11 yr prior, we identify several matched Zeeman pairs. We found no significant changes of magnetic field strengths, directions, or radial velocities from the matched Zeeman pairs between these two epochs (although there were small internal proper motions). This implies quite stable physical conditions in this region. Moreover, we also analysed the physical conditions from the coincidence of OH maser features from different transitions based on current OH maser models.